2018
DOI: 10.1177/0898264318782096
|View full text |Cite
|
Sign up to set email alerts
|

From Snapshots to Movies: The Association Between Retirement Sequences and Aging Trajectories in Limitations to Perform Activities of Daily Living

Abstract: The conventional model in which people completely retire from a full-time job at normative ages and the widely promoted new conventional model of late retirement are both associated with better functioning than early labor force disengagement. But unconventional models, where older adults keep partially engaged with the labor force are also significantly associated with better functioning. These findings call attention to more research on potential avenues to simultaneously promote productive engagement and he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 40 publications
(72 reference statements)
1
10
0
Order By: Relevance
“…Future research could explore differences in other health-related outcomes and the effects of retirement timing by other policy-relevant variables, such as job quality, partial retirement, pension adequacy and lifelong learning. Generating work environments that reinforce health, promoting partial retirements, improving the availability and generosity of old-age pensions, and promoting lifelong learning might constitute additional opportunities to improve health for older adults and to facilitate healthier transitions into retirement (Calvo, 2016;Staudinger et al, 2016;Azar et al, 2018;Calvo et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Future research could explore differences in other health-related outcomes and the effects of retirement timing by other policy-relevant variables, such as job quality, partial retirement, pension adequacy and lifelong learning. Generating work environments that reinforce health, promoting partial retirements, improving the availability and generosity of old-age pensions, and promoting lifelong learning might constitute additional opportunities to improve health for older adults and to facilitate healthier transitions into retirement (Calvo, 2016;Staudinger et al, 2016;Azar et al, 2018;Calvo et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Concretely, first, McDonough and colleagues (2017) found that downshifting from full- to part-time work at the FPA was associated with the most favorable self-rated health among American men. Second, Azar, Staudinger, Slachevsky, Madero-Cabib, and Calvo (2019) observed that a gradual retirement from the labor force was associated with fewer limitations when performing activities of daily living in old age. Third, Diaz-Toro and colleagues (2018) found that individuals who exited the labor force before or around the FPA were more likely to experience heart disease and stroke in their 70s than those who extended working life beyond the FPA.…”
mentioning
confidence: 99%
“…Consistent with findings from the English Longitudinal Study of Ageing (Di Gessa et al, 2017), this suggests that delaying retirement does not benefit health once other factors are accounted for. Note, however, that we only measure age of full retirement; recent evidence from the Health and Retirement Study suggests that later, partial retirement may result in better functional health and slower decline in health in later life (Azar, Staudinger, Slachevsky, Madero-Cabib, & Calvo, 2019). Instead, retirement type proved a much stronger predictor of post-retirement health.…”
Section: Discussionmentioning
confidence: 99%